2014
DOI: 10.4239/wjd.v5.i6.747
|View full text |Cite
|
Sign up to set email alerts
|

Is the present cut-point to define type 2 diabetes appropriate in Latin-Americans?

Abstract: The diagnosis of diabetes mellitus type 2 (DM2) is based either on increased plasma glucose or Glycated hemoglobin levels. Since these measures are the only means for diagnosis of DM2, they must be well adapted to each population according to their metabolic characteristics, given that these may vary in each population. The World Health Organization (WHO) determined the cut-points of plasma glucose levels for the diagnosis of DM2 by associating hyperglycemia with the risk of a specific microvascular complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…After an extensive review of epidemiological evidence, a cutoff of HbA1c !6.5% (48 mmol/mol) for the diagnosis of diabetes was recommended by an International Expert Committee and ADA as optimal for detecting retinopathy [11,25]. Subsequently, many studies demonstrated that racial disparities in HbA1c affected the performance of HbA1c for diagnosing diabetes with a threshold of 6.5% (48 mmol/ mol) [9,16,17]. Several studies showed that the optimal HbA1c cutoff for diagnosing diabetes was between 5.6% (38 mmol/ mol) and 6.3% (45 mmol/mol) in Asian patients [26][27][28], which was lower than the ADA recommended HbA1c threshold for Western populations and largely consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After an extensive review of epidemiological evidence, a cutoff of HbA1c !6.5% (48 mmol/mol) for the diagnosis of diabetes was recommended by an International Expert Committee and ADA as optimal for detecting retinopathy [11,25]. Subsequently, many studies demonstrated that racial disparities in HbA1c affected the performance of HbA1c for diagnosing diabetes with a threshold of 6.5% (48 mmol/ mol) [9,16,17]. Several studies showed that the optimal HbA1c cutoff for diagnosing diabetes was between 5.6% (38 mmol/ mol) and 6.3% (45 mmol/mol) in Asian patients [26][27][28], which was lower than the ADA recommended HbA1c threshold for Western populations and largely consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past four decades, although there have been significant changes in the diagnostic and classification criteria for diabetes and prediabetes, the most widely accepted diagnostic test remains the fasting plasma glucose and the 2-h plasma glucose by an oral glucose tolerance test (OGTT) [9]. However, the use of the OGTT for the diagnosis of diabetes was discouraged for use in clinical settings due to its inconvenience, high cost, and poor reproducibility [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…While several prospective cohort studies suggested that this test was a convenient and effective method for screening DM2 [ 17 20 ], several other studies in diverse populations have disputed the utility of HbA1c based on its similar sensitivity and specificity as FPG in screening for new cases of DM2 and its inferiority to the OGTT as a confirmatory test [ 21 25 ]. In addition, significant differences in HbA1c cut-off points for DM2 according to ethnicity, age, sex, and population prevalence of diabetes were noted [ 7 , 8 ]. In US adults Karnchanasorn et al [ 9 ] reported also found that HbA1c ≥ 6.5% had a low diagnostic capacity relative to both FPG and OGTT, suggesting that a substantial number of cases of DM2 would be missed using this criterion.…”
Section: Discussionmentioning
confidence: 99%
“…The ADA guideline has taken this issue in to account and recommends that when two tests are performed and just one is above the cut-off point, the same test should be repeated to confirm the diagnoses, rather than performing an additional screening test [ 6 ]. Although the risk factors [ 7 ] and the criteria for the diagnosis of DM2 are well defined [ 5 , 6 ], there is ongoing debate as to whether these criteria are universally associated with the future risk of vascular complications [ 8 ]. Furthermore, a recent study found that based on the current cut-points, HbA1c, had a poor capacity to detect DM2 in US adults relative to OGTT and FPG [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, UKPDS data in patients with recent-onset DM2 who received metformin had fewer CV events 35,36 , which suggests that our prediabetic patients may also have benefited from metformin treatment not only via a decrease the progression from prediabetes to DM2, but also by a reduction in CV events. These data have served to question the utility of the blood glucose cut-off points currently used in low-and middleincome countries for the diagnosis of DM2, which were based on a Finnish study that evaluated the association of glycemia with retinopathy, not CV outcomes 63 . A research group in London 64,65 elegantly demonstrated the "point of no return" during the course of peripheral neuropathy, cardiomyopathy, and diabetic nephropathy, when chronic hyperglycaemia causes functional alterations and structural alterations.…”
Section: What Do the Guidelines Say About Prediabetes?mentioning
confidence: 99%